“La relación escuela-familia y aprendizaje” - Iza Tasinchano, Gladys Rosa (2021)
Society has established from its beginning basic forms of interrelation for a better coexistence, whether in the family, community, economic and educational fields. In this sense, an important function is established between teachers and parents, because from a clear, constant and fluid communication brings great benefit to the integral formation of the individual and his or her learning. The purpose of this research study was to analyze the school-family relationship through a life story in order to strengthen the learning of fifth graders of the ‘San José de Guaytacama’ Educational Unit, Province of Cotopaxi, Latacunga Canton, Guaytacama Parish, Santana Neighborhood. The methodology used was qualitative research, because it describes the characteristics of the subjects studied and interprets the information collected on the school-family relationship and learning in the school context; relevant information was obtained through the interview technique, and the instrument used was the interview guide. The proposal was the construction of a life story, which was disseminated to the children’s parents by means of a video, in order to help the family to create communication links with the school, in school activities and coexistence. In terms of the results obtained, it was identified that parents have a great influence on children’s personal and academic development. It is concluded that the school-family relationship in the students’ learning has deteriorated over time in most educational institutions.